Therapeutic Benefits of Short-Arm Human Centrifugation in Multiple Sclerosis–A New Approach - Kourtidou-Papadeli, Chrysoula; Frantzidis, Christos A.; Bakirtzis, Christos; Petridou, Anatoli; Gilou, Sotiria; Karkala, Aliki; Machairas, Ilias; Kantouris, Nikolaos; Nday, Christiane M.; Dermitzakis, Emmanouil V.; Bakas, Eleftherios; Mougios, Vassilis; et al. (Frontiers in Neurology, 2022)
Short-arm human centrifugation (SAHC) is proposed as a robust countermeasure to treat deconditioning and prevent progressive disability in a case of secondary progressive multiple sclerosis. Based on long-term physiological knowledge derived from space medicine and missions, artificial gravity training seems to be a promising physical rehabilitation approach towards the prevention of musculoskeletal decrement due to confinement and inactivity. So, the present study proposes a novel infrastructure based on SAHC to investigate the hypothesis that artificial gravity ameliorates the degree of disability. The patient was submitted to a 4-week training programme including three weekly sessions of 30 minutes of intermittent centrifugation at 1.5 to 2 g. During sessions, cardiovascular, muscle oxygen saturation (SmO2) and electroencephalographic (EEG) responses were monitored, whereas neurological and physical performance tests were carried out before and after the intervention. Cardiovascular parameters improved in a way reminiscent of adaptations to aerobic exercise. SmO2 decreased during sessions concomitant with increased g load, and, as training progressed, SmO2 of the suffering limb dropped, both effects suggesting increased oxygen use, similar to that seen during hard exercise. EEG showed increased slow and decreased fast brain waves, with brain reorganisation / plasticity evidenced through functional connectivity alterations. Multiple-sclerosis-related disability and balance capacity also improved. Overall, this study provides novel evidence supporting SAHC as a promising therapeutic strategy in multiple sclerosis, based on mechanical loading, thereby setting the basis for future randomized controlled trials.